(untitled) (Architecture Image Studies, 2025)
This research investigated the predictive relationship between Creative self-efficacy and Spatial visualization ability among gifted high school students in Saudi Arabia, in light of the knowledge transformation required to achieve the Kingdom’s Vision 2030. The study utilized Bandura’s social-cognitive theory framework to address a notable gap in Arabic literature regarding the interplay between cognitive experience and affective belief. The study used a descriptive correlational approach, applying the Revised PSVT:R and the Creative Self-Efficacy Scale to a sample of gifted high school students. The descriptive results showed that the sample had very high levels of both creative self-efficacy and spatial visualization ability, confirming the superior affective and cognitive characteristics of this group. The results of the correlation analysis showed a positive and statistically significant correlation between creative self-efficacy and spatial visualization ability. (r = 0.48, p < 0.001). More importantly, linear regression analysis revealed that spatial visualization ability statistically significantly predicts creative self-efficacy (B= 0.49, p < 0.001), with spatial visualization explaining approximately 23% of the variance in creative self-efficacy among gifted students. The study concludes that cognitive superiority in spatial ability acts as a cognitive lever that enhances students’ affective confidence in their ability to innovate, supporting the hypothesis of reciprocal interaction between creative self-efficacy and spatial visualization ability. The study recommends the integration of intensive and systematic spatial visualization training programs into gifted education curricula, not only to improve technical skills, but also to enhance their creative self-efficacy and support the development of creative human capital to achieve national development goals.